"Monopoly and its types" (Texas Journal of Multidisciplinary Studies, 2022)
Although the origin of the term monopoly is derived from market concepts, its economic basis is in fact rooted in production. Monopolies can be defined as: monopolies are associations of large enterprises that dominate industries, markets, and the overall macro economy in order to set high prices and monopolize high profits. So, in this article you will have a general idea about monopoly and its types